(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Hydrocephalus in children is a condition in which there is excessive accumulation of cerebrospinal fluid (CSF) in and around the brain and spinal cord. Hydrocephalus in most of the circumstances is congenital hence, would be detected early in pregnancy by various available imaging techniques, thus, terminating pregnancy in the initial stage itself and thereby avoiding mental agony to parents. Death due to hydrocephalus is a rare entity especially that produced in the post natal period. One such case of a 18 month old male baby who was subjected for autopsy at Department of Forensic Medicine, M.S.Ramaiah Medical College with alleged history of birth trauma due to wrong forceps application in a private hospital at the time of delivery is being discussed here.